Navigating the cultural geography of indigenous peoples’ attitude toward genetic research: the Ohana (family) heart project - May Vawer; Patsy Kaina; Ann Leonard; Michael Ogata; Beth Blackburn; Malia Young; Todd B. Seto (International Journal of Circumpolar Health, 2013)
Background . Little is known about the burden of heart failure among indigenous populations, including Native Hawaiians (NH). Recent concerns about genetic research in the NH community resonate with similar concerns raised by American Indian, Alaskan Native and Canadian First Nations communities and have raised questions about the best way to proceed with studies involving biological specimens. Objective . To help us plan a study to investigate disparities in heart failure incidence and outcomes in a NH community, we performed a qualitative study to examine the community's expectations for heart failure research that includes the collection of biological specimens. Methods . Eighty-five NH with a personal or family history of heart failure, who lived in a geographically isolated community in the state of Hawai‘i participated in 1 of 16 semi-structured interviews. Interviews were conducted in a standard manner, with open-ended questions designed to explore their expectations for a heart failure research study that included the collection of biological specimens. Interviews were analyzed thematically through iterative readings and coding. †Deceased. Results . Four key themes regarding heart failure research with the use of biological specimens characterized their expectations: (a) Need to foster trust between investigator and community; (b) Establish a partnership with the community to identify needs and goals; (c) Need for mutual benefit to investigator and community; (d) Identification of a key voice to represent the community. Participants expressed strong support for research. However, the strength of that support was directly related to the strength of the relationship between the research team and the community. The collection of biological specimens for genetic analyses was not an explicit concern or barrier per se. Conclusions . It appears feasible to conduct a heart failure research study that includes the collection of biological samples. However, success will likely require addressing the community's expectations, including the need for a long-term partnership built on trust and mutual benefit, and a key voice to represent the community.